Enhancing OTIF Solution Performance by Analyzing Mechanic Assignment Based on Specialization - Riki Rinaldo; Aditya Tirta Pratama; Yunita Umniyati (Fakultas Teknik Universitas Islam Makassar, 2026)
This research investigates the impact of assigning mechanics according to their specialization on improving maintenance performance and achieving the On Time In Full (OTIF) Solution target at PT ABCD, AIUEO branch. The OTIF Solution achievement dropped drastically from 98.36% in 2023 to 77.92% in 2024, far below the company’s 90% target. The study applies the DMAIC methodology (Define, Measure, Analyze, Improve, Control) using operational data from January to December 2024, including mechanic availability, skill composition, and unit breakdown history. The results demonstrate that specialization-based assignments significantly accelerate repair processes, reduce downtime, and improve OTIF performance to approach the set target. These findings confirm that competency-based human resource management directly contributes to cost efficiency and customer satisfaction.